2009
DOI: 10.1002/jor.20981
|View full text |Cite
|
Sign up to set email alerts
|

GDF‐5/7 and bFGF activate integrin α2‐mediated cellular migration in rabbit ligament fibroblasts

Abstract: Cellular activities responding to growth factors are important in ligament healing. The anterior cruciate ligament (ACL) has poor healing potential compared to the medial collateral ligament (MCL). To assess the differences, we investigated the proliferation, migration, adhesion, and matrix synthesis responding to growth factors in rabbit ACL and MCL fibroblasts. ACL cell proliferation to basic fibroblast growth factor (bFGF), bone morphogenetic protein-2, growth and differentiation factor (GDF)-5, and GDF-7 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…The synovial sheath and fat tissue of ligaments were removed. The midsubstance cores of ACL and MCL were digested using collagenase (Sigma) as described [8]. Attached cells (passage 0) were maintained with Dulbecco's modified Eagle's medium (DMEM, Wako) containing fetal bovine serum (HyClone) and penicillin/streptomycin (Sigma) at 37°C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synovial sheath and fat tissue of ligaments were removed. The midsubstance cores of ACL and MCL were digested using collagenase (Sigma) as described [8]. Attached cells (passage 0) were maintained with Dulbecco's modified Eagle's medium (DMEM, Wako) containing fetal bovine serum (HyClone) and penicillin/streptomycin (Sigma) at 37°C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that growth factor-stimulated cellular migration is slower in ACL than in MCL fibroblasts [8]. In addition, we have identified chondroblastic interface cells derived from the ACL-to-bone insertion [9].…”
Section: Introductionmentioning
confidence: 91%
“…Inner and outer meniscus cells were prepared, respectively, by collagenase (Sigma, St. Louis, MO) treatment. 30 Attached cells (passage 0) were maintained with Dulbecco's modified Eagle's medium (Wako, Osaka, Japan) containing 10% fetal bovine serum (HyClone, South Logan, UT) and 1% penicillin/ streptomycin (Sigma). Meniscus cells between passage 2 and 4 were used.…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…Alexa Fluor 488-conjugated antibody (Invitrogen, Carlsbad, CA) and Alexa Fluor 568 phalloidin (Invitrogen) were used for detection under a fluorescence microscope (1:100 for 20 min). 30 A bovine serum albumin solution without the primary antibody was used as a negative control. Cell extracts were prepared with SDSlysis buffer.…”
Section: Immunohistochemistry Western Blot (Wb) and Immunoprecipitamentioning
confidence: 99%
“…PCR amplification was performed in the presence of 10 pmol of each specific primer. The primer sets for rabbit Col1a1, Col3a1, glyceraldehyde-3-phosphate dehydrogenase (G3pdh) were used [14,27]. The cycle number was selected in the linear part of the amplification curve.…”
Section: Injury Model and Growth Factor Treatmentmentioning
confidence: 99%